First-in-human randomized clinical trials of the safety and efficacy of tanezumab for treatment of chronic knee osteoarthritis pain or acute bunionectomy pain. (May 2018) - Walicke, Patricia A.; Hefti, Franz; Bales, Roxanne; Lu, Shiao-Ping; Ruckle, Jon L.; Brown, Mark T.; West, Christine R.; Shelton, David L.
Abstract: Introduction: The neurotrophin nerve growth factor has a demonstrated role in pain transduction and pathophysiology. Objectives: Two randomized, double-blind, placebo-controlled, phase 1 studies were conducted to evaluate safety, tolerability, and analgesic efficacy of single doses of tanezumab, a humanized anti–nerve growth factor monoclonal antibody, in chronic or acute pain. Methods: In the first study (CL001), patients with moderate to severe pain from osteoarthritis (OA) of the knee received a single intravenous infusion of tanezumab (3–1000 μg/kg) or placebo in a dose-escalation (part 1; N = 42) or parallel-arm (part 2; N = 79) study design. The second study (CL002) was a placebo-controlled dose-escalation (tanezumab 10–1000 μg/kg; N = 50) study in patients undergoing bunionectomy surgery. Results: Adverse event rates were generally similar across treatments. Most adverse events were generally mild to moderate in severity and no patients discontinued as a result of adverse events. Adverse events of abnormal peripheral sensation were more common with higher doses of tanezumab (≥100 μg/kg) than with placebo. These were generally mild to moderate in severity. Tanezumab provided up to 12 weeks of effective analgesia for OA knee pain, with statistically significant improvements at doses ≥100 μg/kg ( P < 0.05). By contrast, no trend for analgesic activity was found when tanezumab was administered 8 to 16 hours before bunionectomy. Conclusions: The demonstration of a favorable safety profile and clinical efficacy in OA pain supports clinical development of tanezumab as a potential treatment for chronic pain conditions. Abstract : Supplemental Digital Content is Available in the Text.